Purchase intention of tourism products and services promoted through Facebook among millennial in Malaysia / Ivyany Hindirek Hendirek ... [et al.] - Hendirek, Ivyany Hindirek; Abdul Satal, Mira Suzana; Lorin, Viviana; Mohd Zaidi, Nur Murniza; Mohamad Musa, Nurafiqah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
This study aims to find out the extent of the effectiveness of the use of social media in promoting tourism products that can attract the attention and trust of customers to buy packages through social media. The study is significant for the tourism industry players to identify their potential customers from Facebook users. Data collection process was conducted through the dissemination of questionnaire which is by using google form for the social media users who have used the social media services in purchasing travel agency's packages via websites. The research used quantitative and descriptive research design. Questionnaire is divided into two parts whereby Part A is about demographic profile, and Part B is on the intention to purchase tourism products and services through Facebook. Data analysis was carried out by using the Statistical Package for Social Sciences (SPSS) version 24. As a result of the survey, there are several answers that were provided by the users, one of which is that they are satisfied with the purchase of travel agency packages online because it saves time. Meanwhile, there are also customers who are less satisfied and have refused to use the social media to buy these packages because they cannot negotiate on the packages that they want. From the analysis conducted, it has made it easier to understand the extent to which the use of social media can help in promote the travel agency packages. Also, it shows that most of the Facebook users in Malaysia are from millennials generation who are more likely to purchase tourism products and services promoted on social media.